Community-Based Ecotourism and Perceived Economic Impacts: A Study of Rural Settlements around Annapurna Conservation Area, Nepal - Bhatta, Kishan Datta (Journal of Engineering Technology and Planning, 2023)
Community-based ecotourism, as a subset of sustainable tourism, is advocated as a tool for community development in the mountain settlements. In this regard, this research adopted exploratory and descriptive approach to investigate the perceived economic impacts of community-based ecotourism in the local communities of Annapurna Conservation Area (ACA) in Nepal. The settlements of Dhampus, Landruk and Ghandruk along the Annapurna Sanctuary Trail (AST) are considered as a case to critically examine the economic impacts of community-based ecotourism development on local residents both residing along the major trail (MT) and off the trail (OT) in the ACA. Multiple methods of data collection such as questionnaire survey with households, key informants interview, participant observation, informal discussion with local entrepreneurs and residents, and archival research have been conducted. Research findings showed that community-based ecotourism has provided extensive economic benefits to local people, however in a varying degree. It has provided economic benefits to local communities and enhanced local economy, however not all residents receive benefits equitably. People living along the MT (i.e. mostly the tourism entrepreneurs) receive higher economic benefits than that of OT (i.e. mostly the farmers). The farmers, low-wage employees, and marginalized community receive lowest benefits but largely influenced by the inflation and tourism impacts. In addition, there seem economic leakages, weak integration of local products into tourism system and inflation. This study stresses on the inclusive participation of local people in the planning and decision making of tourism development as well as sharing of benefits while also reducing the economic leakages and strengthening its linkages.